Pharmacoepidemiological survey of schizophrenia in Central India - Rode, Sonali B.; Salankar, Harsh V.; Verma, Pravin R.; Sinha, Umesh; Ajagallay, Rajesh K. (International Journal of Research in Medical Sciences, 2017)
Background:Schizophrenia is a chronic and debilitating psychiatric illness affecting around 0.3-0.7% of people at some point in their life. The rate of schizophrenia and related disorders is affected by some environmental factors and social variables. Therefore, pharmacoepidemiological survey of patients suffering from schizophrenia was carried out to analyze the sociodemographic profile and drug prescribing pattern. Methods:A prospective observational study was conducted in psychiatry OPD of a tertiary care hospital for nine months. Diagnosis of schizophrenia was made according to DSM IV-TR criteria. Prescriptions were analyzed for socio demographic details, distribution of subsets of disease and psychotropic drugs prescribed. Results:Amongst 196 cases analyzed, 55.61% were males, 69.9% were below 40 years, 52.04% unmarried, 61.22% belonged to low income group, 82.14% unemployed and 58.16% came from urban locality. Paranoid schizophrenia (79.59%) was the most common diagnosis and a total of 402 psychotropic drugs were prescribed. Average number of psychotropic drugs per prescription was 2.05. Atypical antipsychotics (80.09%) were prescribed more commonly than typical antipsychotics; olanzapine (42.48%) was the commonest antipsychotic drug followed by risperidone (21.68%), haloperidol (19.91%), quetiapine (7.96%), aripiprazole (4.42%) and clozapine (3.54%). As an adjunctive treatment escitalopram, clonazepam and carbamazepine were the commonly prescribed antidepressant, anxiolytic and antimanic agent respectively. Conclusion:Low socioeconomic status, unemployment, urban locality and living alone are the sociodemographic factors associated with schizophrenia. The treatment pattern observed correlates with the changing trends in the treatment of schizophrenia world over.